Between Advisory and Assurance : Exploring the Structure and Ethical Boundaries of the ESG Services Market in the Czech Republic - Peterka, Simon (2025)
This thesis maps the emerging market for ESG consulting and auditing in the Czech Republic, detailing who provides which services, how advisory and assurance are organizationally separated, and what safeguards exist to preserve their independence. A mixed-method design—public-document analysis of 20 firms followed by ten interviews with professionals yields a granular picture of service portfolios, team hierarchies and data practices. Interpreted through agency, signaling and legitimacy theory, the evidence reveals fragmented data ownership, limited-scope assurance frequently delivered by the same networks that draft reports, and incentive structures favoring procedural compliance over decision-useful insight. EU regulation acts as the dominant demand trigger yet leaves firms struggling to define assurance scope and data stewardship. Actor-specific recommendations follow board-level ESG data stewards and incentive realignment for companies, phased scoping and partner rotation for advisory networks, and sector-based templates plus stricter conflict-of-interest registers for regulators. The study provides the first systematic map of Czech ESG services, extends theorizing to a transition economy and offers a practical reform roadmap.